Improving maternal outcomes of young mothers through mobile health (mHealth) and community-based interventions: Evidence from a quasi-experimental trial in Kwale County, Coastal Kenya - Jefferson Mwaisaka; John Ganle; Adom Manu; Kwasi Torpey (PLoS ONE, 2025)
Background Inefficient referral systems and limited awareness on the importance of antenatal care (ANC) hinder expectant adolescents and young women from achieving the recommended ANC visits. Mobile health interventions and community-based clinical outreaches have emerged as potential strategies to improve ANC utilization and skilled delivery rates. Objective This study evaluates the effectiveness of mHealth text messaging and community-based clinical outreaches in improving ANC uptake, skilled deliveries, and infants’ birthweights among expectant adolescents and young women in Kwale County, Coastal Kenya. Methods A quasi-experimental study was conducted across four public health facilities, comparing three groups: mHealth text messaging intervention, community-based outreaches, and a control group receiving standard care. Multivariate regression models were used to adjust for baseline differences and potential confounders. Key outcomes included ANC attendance, skilled birth attendance, and infant birthweights. Results A total of 817 participants were included in the analysis. Participants in the mHealth (RR: 0.5 [95% CI: 0.4–0.7], p < 0.001) and outreach arms (RR: 0.1 [95% CI: 0.0–0.7], p = 0.024), had significantly lower risk of low ANC contacts compared to the control arm participants. Similarly, the odds of unskilled deliveries were significantly lower in the mHealth (OR: 0.2 [95% CI: 0.1–0.4, p < 0.001] and the outreach arms (OR: 0.1 [95% CI: 0.0–0.6], p = 0.007), compared to the control group. Notably, infants born to participants in the mHealth-text message intervention (OR: 5.9 [95% CI: 1.7–20.8, p = 0.006]) and outreach arms (OR: 6.6 [95% CI: 1.7–25.7], p = 0.007) had significantly higher odds of low birth weight, compared to those born to control arm participants. Conclusions Both mHealth-text messaging and community-based clinical outreaches can improve antenatal contacts and institutional skilled deliveries. Integrating both strategies can enhance maternal health outcomes for young women in Kenya and should be considered for broader adoption within public health programs to optimize care delivery.